All that is solid melts into air : the experience of modernity - Berman, Marshall (Verso Books, 2010)
Marshall Berman's "All that is solid melts into air" is widely acclaimed as one of the greatest books on modernity. A kaleidoscopic journey into the experiences of modernization, the dizzying social changes that swept millions of people into the capitalist world, it dexterously interweaves an exploration of modernism in art, literature, and architecture.